Corrugated board multi-composite network adhesive and preparation and use methods thereof

By constructing a corrugated cardboard adhesive with a multi-layer cross-linked network, the problems of stability, moisture resistance, and heat resistance of starch-based adhesives have been solved, achieving high-strength, water-resistant, and mildew-resistant corrugated cardboard bonding and reducing production costs.

CN121086701APending Publication Date: 2025-12-09宿迁科佳环保科技有限公司
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202511337413.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-18
Publication Date
2025-12-09

AI Technical Summary

Technical Problem

Existing starch-based adhesives have problems in corrugated cardboard production, such as poor stability, poor moisture resistance, slow drying speed, insufficient initial tack, and limited high-temperature resistance, which affect production efficiency and product quality.

Method used

A multi-composite network adhesive is adopted, which constructs a multi-crosslinked network of covalent bonds, coordination bonds, hydrogen bonds and ionic bonds through components such as waxy corn starch, industrial alkali lignin, chitosan, nanocellulose and borate ester compounds. Combined with pH adjustment and preservatives, a stable adhesive system is formed.

Benefits of technology

It significantly improves the cohesive strength, heat resistance and creep resistance of adhesives, enhances moisture resistance and mildew resistance, extends service life and reduces raw material costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a multi-composite network adhesive for a corrugated board. The multi-composite network adhesive comprises the following components in parts by mass: 100-120 parts of waxy corn starch, 20-25 parts of industrial alkali lignin, 3-5 parts of chitosan, 2-3 parts of a borate compound, 5-8 parts of nano cellulose (CNF), 0.5-3 parts of borate, 1.5-2.5 parts of a synergistic preservative and 1-5 parts of a filler / pH buffering agent, the other components comprise a pH regulator, weak organic base and a solvent, and then a perfect preparation process and a perfect use method are provided. The high-strength, water-resistant, mildew-proof and stable corrugated board adhesive has the beneficial effects that the high-strength, water-resistant, mildew-proof and stable corrugated board adhesive is successfully prepared through a constructed multiple physical / chemical cross-linked network, the comprehensive performance of the adhesive is far better than that of the prior art, meanwhile, when the adhesive is used for corrugated boards, recycling of the corrugated boards is facilitated, low-cost renewable substances are used, and the environment-friendly effect is achieved. The production cost is effectively reduced, the environmental protection property is good, and many defects of the existing adhesive are perfectly solved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of corrugated paperboard bonding, in particular to a corrugated paperboard multi-composite network adhesive and its preparation and use method. BACKGROUND

[0002] Starch-based adhesives (usually using corn or cassava starch as raw material) are the most mainstream type of adhesive in the production of corrugated paperboard due to their low price, good adhesion and environmental protection. However, they also have some obvious shortcomings. Poor stability is the most common problem, as the viscosity is unstable, it can easily become diluted during use, and it can easily separate and precipitate when stored, making it difficult to use continuously. This can lead to difficulty in controlling the gluing process, affecting the stability of product quality. Poor moisture resistance, corrugated paperboard made from starch glue is prone to moisture absorption and moisture regain in a humid environment, causing the paperboard to become soft and the adhesive strength to decrease, and even to delaminate. This is a serious test for packaging that needs to be refrigerated, shipped by sea, or stored and transported in a high-humidity environment.

[0003] Slow drying speed, affecting production efficiency, the drying speed of starch glue is relatively slow, in order to ensure the firmness of the paperboard, the production speed may have to be reduced, or a long time is still needed after the drying channel to completely dry, the paperboard is stacked after not dry, the moisture is difficult to volatilize, it may be reabsorbed by the paperboard, causing the paperboard to become soft, deformed or delaminate later.

[0004] The initial adhesion of starch glue is sometimes poor, on high-speed production lines, the glue may be separated due to the movement of the paperboard before it has fully penetrated and gelatinized, causing "run corrugation" or "hollow" phenomenon.

[0005] Starch glue needs to reach a certain gelatinization temperature to develop adhesion. If the temperature is not properly controlled, for example, if the gelatinization is too fast, the glue may not be able to fully penetrate the paper; and if the gelatinization is too slow, the glue may be over-permeated, making it impossible to form effective adhesion.

[0006] Hot melt glue (such as EVA-based) has fast curing speed, and is suitable for automatic sealing box and other high-speed production lines. However, its high-temperature resistance is limited, and it may soften and lose adhesion in high-temperature environment, and may become brittle in low-temperature environment. In addition, compared with ordinary starch glue, the raw material cost may be higher. Hot melt glue (such as EVA-based) has fast curing speed, and is suitable for automatic sealing box and other high-speed production lines. However, its high-temperature resistance is limited, and it may soften and lose adhesion in high-temperature environment, and may become brittle in low-temperature environment. In addition, compared with ordinary starch glue, the raw material cost may be higher. Sodium silicate-based adhesive (sodium silicate / water glass) can increase the stiffness of paperboard in a short period of time, but has very outstanding problems, and has been banned by the state, but a small amount is still used: it is very easy to be damp, and after being damp, the paperboard is easy to open and soften, which leads to a significant decrease in edge compression strength, and the stored cartons often collapse, which has a negative impact on the quality of the cartons, and can cause the cartons to discolor, form white frost, deform and break, etc. And it is toxic to the human body and the environment. SUMMARY

[0007] In view of the above problems, the present application solves the above problems by the following technical scheme.

[0008] A corrugated paperboard multi-repeated network adhesive comprises the following components by mass fraction:

[0009] 100-120 parts of waxy corn starch, 20-25 parts of industrial alkali lignin, 3-5 parts of chitosan, 2-3 parts of borate ester compound, 5-8 parts of nanocellulose (CNF), and 0.5-3 parts of borate,

[0010] 1.5-2.5 parts of synergistic preservative, and 1-5 parts of filler / pH buffer;

[0011] The remaining components include a weak organic base pH adjuster and a solvent.

[0012] Further, the weak organic base pH adjuster is triethanolamine TEA, which is not added by parts, and is used to accurately adjust the pH of the whole system to the optimal range of 9.5-10.5.

[0013] Further, the solvent is deionized water, which is not added by parts, and is adjusted to a final adhesive solid content of 20-25wt%.

[0014] Further, the borate is a complex component including borax and zinc borate, and the mass ratio of the borax to the zinc borate is 1.2-1.5:1.

[0015] Further, the borate ester compound is 1,3-benzenediol diboronic acid.

[0016] Further, the synergistic preservative includes 0.3-0.5 parts of copper sulfate and 1.2-2 parts of catechol.

[0017] Further, the filler is magnesium hydroxide 1-5 parts.

[0018] Further, the chitosan is dissolved in 1% (v / v) aqueous acetic acid.

[0019] A preparation method of a corrugated paperboard multiple composite network adhesive, comprising the following steps:

[0020] S1. Raw material pretreatment

[0021] I. Preparation of chitosan acid solution:

[0022] Take the formula amount of deionized water, prepare 1% (v / v) acetic acid aqueous solution, slowly add the corresponding mass fraction of chitosan powder to the continuously stirred acetic acid solution in container A, and stir vigorously until completely dissolved to obtain a clear or slightly turbid viscous solution. Standby after degassing.

[0023] II. Preparation of magnesium hydroxide suspension:

[0024] In container B, mix the corresponding mass fraction of magnesium hydroxide powder with a small amount (about 20 parts) of deionized water, and use a high-shear disperser to pre-disperse for 15 minutes to form a uniform and stable suspension for standby.

[0025] III. Preparation of borate premix solution:

[0026] According to the proportion (borax: zinc borate = 1.2-1.5:1), the total borate is weighed and dissolved with appropriate warm water to obtain a clear solution for standby;

[0027] According to the proportion (borax: zinc borate = 1.2-1.5:1), the corresponding mass fraction of total borate is weighed and dissolved with appropriate warm water (about 50°C) to obtain a clear solution. Zinc borate has low solubility, so it needs to be stirred patiently or slightly heated to completely disperse;

[0028] S2. Paste gelatinization of starch / lignin slurry:

[0029] Add about 1 / 3 of the total amount of deionized water to the reaction kettle, start stirring, slowly add the corresponding mass fraction of waxy corn starch and the corresponding mass fraction of industrial alkali lignin, stir for 10 minutes to form a uniform suspension without dry powder, slowly heat to 75-85°C, and keep stirring at this temperature for 20-30 minutes to fully gelatinize the starch. The system becomes uniform and viscous slurry;

[0030] S2. Mixing process:

[0031] Stop heating, let the temperature of the slurry obtained in the previous step drop below 50℃, slowly add the pretreated chitosan acid solution into the reactor, fully stir for 15 minutes to make it evenly mixed, slowly add the pH adjuster triethanolamine (TEA), initially adjust the pH of the system to 8.5-9.0, slowly add the corresponding mass fraction of nanocellulose (CNF) gel, switch to a high shear disperser, shear and disperse at a speed of at least 2000 rpm for 20-30 minutes, to ensure that the CNF is completely dispersed and there is no agglomeration, and the viscosity of the system increases significantly;

[0032] S4. pH adjustment:

[0033] Continue to slowly add TEA, under continuous stirring and cooling (maintain <50℃), accurately adjust the pH of the entire system to the core reaction interval of 9.5-10.5, and confirm with precision pH paper or a pH meter;

[0034] S5. Introduce the core crosslinking network:

[0035] Under continuous moderate stirring, slowly add a solution of 1,3-benzene diol diboronic acid dissolved in anhydrous ethanol, with a concentration of 20%-30% (w / v), continue the reaction for 15 minutes to allow the dynamic covalent crosslinking reaction to proceed initially;

[0036] S6. Add auxiliary crosslinking and preservative:

[0037] Add the pre-prepared borate premix solution, then add the corresponding mass fraction of copper sulfate and catechol, maintain the system temperature <50℃, continue stirring for 20 minutes;

[0038] S7. Build an ionic network and functionalization:

[0039] Slowly add the pre-dispersed magnesium hydroxide suspension, fully stir for more than 3 minutes to ensure that the magnesium ions are evenly dispersed and fully interact with the network;

[0040] S8. Final adjustment and discharge:

[0041] Add the remaining deionized water to adjust the final system solid content to 20%-25wt%, detect the pH again to ensure that it is still within the range of 9.5-10.5, stop stirring, cool to room temperature, discharge, and filter out any possible impurities to obtain the final product, which is sealed and packaged.

[0042] A method for using a corrugated paperboard multiple composite network adhesive, the method comprising the following steps: first, gluing, uniform roller coating with corrugated peaks; second, aging in open air for about 1-3 minutes; third, adhering to the inner paper; fourth, heat pressing and curing, temperature: 120-150 DEG C, pressure: 0.5-1.5 MPa, heat pressing and curing for 90-180 seconds, and fifth, cooling and setting.

[0043] The lignin in the above formula provides rigidity, hydrophobicity and additional reaction sites; the waxy corn starch (almost amylose) provides abundant hydroxyl groups and better film-forming properties, the compound containing borate groups (such as 1,3-benzenediol diboronic acid) forms a covalent network of dynamic borate ester bonds; chitosan (key synergist) stabilizes the borate ester bond through B-N coordination, greatly improving water resistance; enhancing mechanical strength, with natural antibacterial and antiseptic ability; the amino groups on the chitosan chain can form B-N coordination with the borate ester bond, and the molecular chain can also form hydrogen bonds with CNF, starch and the like, playing a dual role of "bridge" and "enhancement", forming a boron-nitrogen coordination bond network; the nanoscale fiber structure of CNF has a large specific surface area and a very high aspect ratio, and can form a very dense hydrogen bond network with all biomass molecules (starch, lignin, chitosan), effectively dispersing stress and preventing crack propagation, thereby greatly improving the initial adhesion, toughness, tensile strength and tear resistance; weak organic alkali (pH adjuster / catalyst) creates and maintains an alkaline environment (pH ~ 9-11), which is the key to forming stable borate ester bonds, and its nitrogen-containing groups (such as organic amines) can participate in B-N coordination, further stabilizing the network; borate (such as borax) auxiliary crosslinking agent (rapidly bonds with starch) and preservative and mildew-proof agent form a synergistic crosslinking network with the core crosslinking agent, optimizing the crosslinking density and curing rate; copper sulfate / catechol as an auxiliary preservative / bactericide, prevents biodegradation and prolongs shelf life, and the catechol structure can strongly interact with boron and participate in crosslinking. Magnesium hydroxide builds a pH buffer system to maintain pH stability and long-term protection of the stability of dynamic borate ester bonds and B-N coordination bonds, and various negatively charged groups in the system undergo ionic bonding or coordination, introducing an ionic bond network on top of the existing covalent bond network (borate ester bond), coordination bond network (B-N) and hydrogen bond network (CNF, etc.). This multi-network interpenetrating structure can greatly improve the cohesive strength, heat resistance and creep resistance (i.e. not easily deformed under sustained stress) of the adhesive.

[0044] The beneficial effects of the present application are: 1. Through the multiple cross-linking network (covalent bond, coordination bond, hydrogen bond and ionic bond) and hydrophobic modification, the adhesive can effectively resist moisture erosion after curing; 2. The unique synergistic corrosion prevention system and the protection of natural components such as starch and chitosan greatly prolong the service life of the adhesive itself and the final paperboard product, prevent mold and biological degradation; 3. Using renewable resources (starch, lignin, chitosan, cellulose) as the main raw material, reducing the dependence on petroleum-based polymers. No formaldehyde release, safer and more environmentally friendly. The formula designs a detailed preparation and use method, the pH and temperature control are clear, and the sizing and hot pressing process of the existing corrugated paperboard production line has good compatibility; 4. A large amount of relatively low-priced biomass raw materials (such as lignin as a partial substitute) are used, which can control the cost of raw materials while improving performance. DETAILED DESCRIPTION

[0045] The technical solutions in the embodiments of the present application will be clearly and completely described below in combination with the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, not all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor are within the scope of protection of the present application.

[0046] A preparation method of a corrugated paperboard multiple composite network adhesive, comprising the following steps:

[0047] S1. Raw material pretreatment

[0048] I. Preparation of chitosan acid solution:

[0049] Take the formula amount of deionized water, prepare 1% (v / v) acetic acid solution, slowly add the corresponding mass fraction of chitosan powder to the continuously stirred acetic acid solution in container A, and stir vigorously until completely dissolved to obtain a clear or slightly turbid viscous solution, and stand for defoaming for standby.

[0050] II. Preparation of magnesium hydroxide suspension:

[0051] In container B, mix the corresponding mass fraction of magnesium hydroxide powder with a small amount (about 20 parts) of deionized water, and use a high-shear dispersing machine to pre-disperse for 15 minutes to form a uniform and stable suspension, and stand for standby.

[0052] III. Preparation of borate premix solution:

[0053] According to the proportion (borax: zinc borate = 1.2-1.5: 1), the total borate is weighed and dissolved with appropriate warm water to obtain a clear solution, and is ready for use.

[0054] According to the proportion (borax: zinc borate = 1.2-1.5: 1), the corresponding mass fraction of total borate is weighed, dissolved with appropriate warm water (about 50℃), and the zinc borate is dissolved at a low solubility, which needs to be stirred patiently or slightly heated to completely disperse, to obtain a clear solution, which is ready for use;

[0055] S2. Paste gelatinization of starch / lignin slurry:

[0056] Add about 1 / 3 of the total amount of deionized water to the reaction kettle, start stirring, slowly add the corresponding mass fraction of waxy corn starch and the corresponding mass fraction of industrial alkali lignin, stir for 10 minutes to form a uniform suspension without dry powder, slowly heat to 75-85℃, and keep stirring at this temperature for 20-30 minutes to fully gelatinize the starch, and the system becomes uniform and viscous slurry;

[0057] S2. Mixing process:

[0058] Stop heating and let the slurry obtained in the previous step cool to below 50℃, slowly add the pretreated chitosan acid solution to the reaction kettle, stir thoroughly for 15 minutes to mix evenly, slowly add the pH adjuster triethanolamine (TEA), and adjust the pH of the system to 8.5-9.0, slowly add the corresponding mass fraction of nanocellulose (CNF) gel, switch to a high shear disperser, and shear disperse at a speed of at least 2000 rpm for 20-30 minutes to ensure complete dispersion of CNF without aggregation, and the viscosity of the system increases significantly;

[0059] S4. pH adjustment:

[0060] Continue to slowly add TEA, and under continuous stirring and cooling (maintain <50℃), accurately adjust the pH of the entire system to the core reaction interval of 9.5-10.5, and confirm with precision pH paper or pH meter;

[0061] S5. Introduce core crosslinking network:

[0062] Under continuous moderate stirring, slowly add a solution of 1,3-benzene diol diboronic acid dissolved in anhydrous ethanol with a concentration of 20%-30% (w / v), continue the reaction for 15 minutes to allow the dynamic covalent crosslinking reaction to proceed initially;

[0063] S6. Add auxiliary crosslinking and preservative:

[0064] Add the pre-prepared borate premix solution, then add the corresponding mass fraction of copper sulfate and catechol, maintain the system temperature <50℃, and continue stirring for 20 minutes;

[0065] S7. Build ionic network and functionalization:

[0066] Slowly add the pre-dispersed magnesium hydroxide suspension, stir for more than 3 minutes to ensure uniform dispersion of magnesium ions and full interaction with the network;

[0067] S8. Final adjustment and discharge:

[0068] Add the remaining deionized water to adjust the final system solid content to 20-25wt%, retest the pH to ensure it is still in the range of 9.5-10.5, stop stirring, cool to room temperature, discharge, filter out the possible few impurities, get the final product, and seal the package.

[0069] A method for using a corrugated paperboard multi-repeated network adhesive, the method comprising the following steps: first, gluing, uniformly rolling and applying to the corrugated peaks; second, aging in open air for about 1-3 minutes; third, adhering to the inner paper surface; fourth, heat pressing and curing at a temperature of 120-150℃ and a pressure of 0.5-1.5MPa for 90-180 seconds; and fifth, cooling and setting.

[0070] Example 1

[0071] Waxy corn starch 100 parts, industrial alkali lignin 20 parts, chitosan 3 parts, borate ester compound 2 parts, nanocellulose (CNF) 5 parts, borate 0.5 parts (the mass ratio of borax to zinc borate is 1.2:1), synergistic preservative 1.5 parts, 0.3 parts of copper sulfate, 1.2 parts of catechol; filler / pH buffer magnesium hydroxide 1 part;

[0072] Example 2

[0073] Waxy corn starch 120 parts, industrial alkali lignin 25 parts, chitosan 5 parts, borate ester compound 3 parts, nanocellulose (CNF) 8 parts, borate 3 parts (the mass ratio of borax to zinc borate is 1.2:1), synergistic preservative 2.5 parts (0.5 parts of copper sulfate, 1.5 parts of catechol), filler / pH buffer 5 parts of magnesium hydroxide;

[0074] Example 3

[0075] Waxy corn starch 100 parts, industrial alkali lignin 20 parts, chitosan 3 parts, borate ester compound 2 parts, nanocellulose (CNF) 5 parts, borate 0.5 parts (the mass ratio of borax to zinc borate is 1.5:1), synergistic preservative 1.5 parts, 0.3 parts of copper sulfate, 1.2 parts of catechol; filler / pH buffer magnesium hydroxide 1 part;

[0076] The manufacturing process of the adhesive of the above examples includes the following steps:

[0077] S1. Raw material pretreatment

[0078] I. Preparation of chitosan acid solution:

[0079] Take the formula amount of deionized water, prepare 1% (v / v) acetic acid solution, in container A, slowly add the corresponding mass fraction of chitosan powder to the continuously stirred acetic acid solution, stir vigorously until completely dissolved, to get a clear or slightly turbid viscous solution, and stand for defoaming for standby.

[0080] II. Preparation of magnesium hydroxide suspension:

[0081] In container B, mix the corresponding mass fraction of magnesium hydroxide powder with a small amount (about 20 parts) of deionized water, and use a high shear disperser to pre-disperse for 15 minutes to form a uniform and stable suspension for standby.

[0082] III. Preparation of borate premix solution:

[0083] According to the proportion (borax: zinc borate = 1.2-1.5:1), the total borate is weighed and dissolved with appropriate amount of warm water to get a clear solution for standby;

[0084] According to the proportion (borax: zinc borate = 1.2-1.5:1), the total borate is weighed and dissolved with appropriate amount of warm water (about 50℃) to get a clear solution for standby;

[0085] S2. Paste gelatinization of starch / lignin slurry:

[0086] Add about 1 / 3 of the total amount of deionized water to the reaction kettle, start stirring, slowly add the corresponding mass fraction of waxy corn starch and the corresponding mass fraction of industrial alkali lignin, stir for 10 minutes to form a uniform suspension without dry powder, slowly heat to 75-85℃, and keep stirring at this temperature for 20-30 minutes to make the starch fully gelatinized, and the system becomes uniform and viscous slurry;

[0087] S2. Mixing process:

[0088] Stop heating and let the temperature of the slurry obtained in the previous step drop below 50℃, slowly add the pretreated chitosan acid solution to the reaction kettle, stir thoroughly for 15 minutes to make it evenly mixed, slowly add the pH adjuster triethanolamine (TEA), and adjust the pH of the system to 8.5-9.0, slowly add the corresponding mass fraction of nanocellulose (CNF) gel, switch to a high shear disperser, and shear disperse at a speed of at least 2000 rpm for 20-30 minutes to ensure that the CNF is completely dispersed without agglomeration, and the viscosity of the system increases significantly;

[0089] S4. pH adjustment:

[0090] Continue to slowly add TEA, under continuous stirring and cooling (maintain <50℃), adjust the pH of the whole system to the core reaction interval of 9.5-10.5, and confirm with precision pH test paper or pH meter;

[0091] S5. Introduce the core crosslinking network:

[0092] Under continuous moderate stirring, slowly add a solution of 1,3-benzene diol diboronic acid dissolved in anhydrous ethanol with a concentration of 20%-30%(w / v), continue the reaction for 15 minutes to allow the dynamic covalent crosslinking reaction to proceed initially;

[0093] S6. Add auxiliary crosslinking and preservative:

[0094] Add the pre-prepared borate premix solution, then add the corresponding mass fraction of copper sulfate and catechol, maintain the system temperature <50℃, continue to stir for 20 minutes;

[0095] S7. Build an ionic network and functionalization:

[0096] Slowly add the pre-dispersed magnesium hydroxide suspension, stir thoroughly for more than 3 minutes to ensure uniform dispersion of magnesium ions and full interaction with the network;

[0097] S8. Final adjustment and discharge:

[0098] Add the remaining deionized water to adjust the final system solid content to 20%-25wt%, detect the pH again to ensure it is still within the range of 9.5-10.5, stop stirring, cool to room temperature, discharge, filter out possible minor impurities, and obtain the final product, which is sealed and packaged.

[0099] A method for using a corrugated paperboard multi-repeated composite network adhesive, the method comprising the following steps: first, applying glue, uniformly coating the corrugated peaks; second, aging in open air for about 1-3 minutes; third, adhering to the inner paper surface; fourth, hot pressing and curing at a temperature of 120℃-150℃ and a pressure of 0.5-1.5MPa for 90-180 seconds; and fifth, cooling and setting.

[0100] To verify the excellent performance of the corrugated paperboard multi-repeated composite network adhesive described in the present application, adhesive samples of Examples 1-3 of the present application were prepared using the above preparation process and method, and were compared with commercially available ordinary starch adhesive and sodium silicate adhesive (soda ash) for testing. The test results are as follows:

[0101] Test samples are:

[0102] Comparative Example 1 (CE-1): commercially available ordinary oxidized starch adhesive (solid content 25%)

[0103] Comparative Example 2 (CE-2): Commercially available sodium silicate adhesive (modulus 3.2, solid content 40%)

[0104] Example 1 (EX-1): Prepared according to the formulation and method of Example 1 of the present application

[0105] Example 2 (EX-2): Prepared according to the formulation and method of Example 2 of the present application

[0106] Example 3 (EX-3): Prepared according to the formulation and method of Example 3 of the present application

[0107] Table 1: Test results of adhesive bulk properties

[0108]

[0109] Table 2: Test results of corrugated board bonding properties (base paper: 125 g / m2boxboard)

[0110]

[0111] Table 3: Test results of corrugated board overall performance and adhesive functionality

[0112]

[0113] From the above test data, it can be seen that the multiple composite network adhesives (EX-1, EX-2, EX-3) provided by the present application are significantly superior to the conventional products of the comparative examples in terms of key performance.

[0114] High initial adhesion and final strength: As shown in Table 2, the initial adhesion strength of the present application is more than 3 times that of Comparative Example 1, and the final bonding strength is nearly doubled. This is due to the reinforcing effect of nanocellulose (CNF) and the rapid construction of multiple networks.

[0115] Excellent water resistance and moisture resistance: This is the most prominent advantage of the present application. After being immersed in water for 24 hours, it still maintains a bonding strength of more than 500 N / m, which is much better than the conventional products (CE-1, CE-2) that are delaminated when they come into contact with water. This verifies the stability of the dynamic covalent borate network and the metal ion crosslinking network in the wet state.

[0116] Excellent storage stability: As shown in Table 1, the viscosity change rate of the product of the present application is less than 10% within 30 days, while the viscosity of the conventional starch adhesive fluctuates greatly and sodium silicate is easily precipitated, indicating that the product of the present application has a longer shelf life and better process stability.

[0117] Significant mold and corrosion prevention effect: In a high temperature and high humidity environment, the product of the present application can achieve 0 or 1 grade mold prevention, while Comparative Example 1 is severely moldy. This proves that the synergistic corrosion prevention system of copper sulfate and catechol plays a key role.

[0118] Good process adaptability: dry curing time is between fast drying but poor sodium silicate and slow drying traditional starch glue, compatible with existing production line, while ensuring the final performance.

[0119] Conclusion: By constructing a "starch-lignin-chitosan-CNF" multiple physical / chemical crosslinking network, a corrugated paperboard adhesive with high strength, water resistance, mildew resistance and stability is successfully prepared, the comprehensive performance is far superior to the prior art, and many industry pain points in the background technology are perfectly solved.

[0120] It is apparent to those skilled in the art that the application is not limited to the details of the foregoing exemplary embodiments, and that the application can be implemented in other concrete forms without departing from the spirit or essential characteristics of the application. Therefore, the embodiments should be considered in all aspects as exemplary and non-limiting, and the scope of the application is defined by the appended claims rather than the above description, and all changes falling within the meaning and range of the equivalent elements of the claims are intended to be included in the application. Any mark in the claims should not be regarded as limiting the claims involved.

[0121] In addition, it should be understood that although the present specification is described in terms of embodiments, not every embodiment contains only one independent technical solution, and the description manner of the specification is only for the sake of clarity, and those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be properly combined to form other embodiments that those skilled in the art can understand.

Claims

1. A multi-layer composite network adhesive for corrugated cardboard, characterized in that: The components include the following parts by weight: 100-120 parts waxy corn starch, 20-25 parts industrial alkali lignin, 3-5 parts chitosan, 2-3 parts borate ester compound, 5-8 parts nanocellulose (CNF), 0.5-3 parts borate, 1.5-2.5 parts synergistic preservative, and 1-5 parts filler / pH buffer. The remaining components include a pH adjuster, a weak organic base, and a solvent.

2. The corrugated cardboard multi-layer composite network adhesive according to claim 1, characterized in that: The pH adjuster, a weak organic base, is triethanolamine (TEA), which is not added according to a specified ratio and is used to precisely adjust the pH of the entire system to the optimal range of 9.5–10.

5.

3. The corrugated cardboard multi-layer composite network adhesive according to claim 1, characterized in that: The solvent is deionized water, which is not added according to the specified parts, and is adjusted to a final adhesive solid content of 20% to 25 wt%.

4. The corrugated cardboard multi-layer composite adhesive according to claim 1, characterized in that: The borate is a compound component comprising borax and zinc borate, wherein the mass ratio of borax to zinc borate is 1.2 to 1.5:

1.

5. The corrugated cardboard multi-layer composite network adhesive according to claim 1, characterized in that: The borate ester compound is 1,3-phenylene glycol diboronic acid.

6. The corrugated cardboard multi-layer composite network adhesive according to claim 1, characterized in that: The synergistic preservative includes 0.3 to 0.5 parts copper sulfate and 1.2 to 2 parts catechins.

7. The corrugated cardboard multi-layer composite network adhesive according to claim 1, characterized in that: The filler is 1 to 5 parts of magnesium hydroxide.

8. The corrugated cardboard multi-layer composite network adhesive according to claim 1, characterized in that: The chitosan was dissolved in a 1% (v / v) aqueous solution of acetic acid.

9. The method for preparing a multi-layer composite network adhesive for corrugated cardboard according to claim 1, characterized in that... Includes the following steps: S1. Raw material pretreatment I. Preparation of chitosan acid solution: Chitosan powder is dissolved in a 1% (v / v) aqueous solution of acetic acid and stirred vigorously until completely dissolved to obtain a clear or slightly turbid viscous solution. The solution is then allowed to stand to remove bubbles before use. II. Preparation of magnesium hydroxide suspension: Mix magnesium hydroxide powder with a small amount (about 20 parts) of deionized water and pre-disperse it for 15 minutes using a high-shear disperser to form a uniform and stable suspension for later use. III. Preparation of borate premix: Weigh out the corresponding mass fractions of total borate according to the ratio (borax:zinc borate = 1.2~1.5:1), dissolve in an appropriate amount of warm water by stirring, and obtain a clear solution for later use; S2. Starch / lignin slurry gelatinization: Add about 1 / 3 of the total amount of deionized water to the reactor, start stirring, slowly add the corresponding mass of waxy corn starch and industrial alkali lignin, stir for 10 minutes to form a uniform suspension without dry powder, slowly heat to 75-85℃, and keep stirring at this temperature for 20-30 minutes to fully gelatinize the starch and make the system a uniform and viscous slurry. S2. Mixing process: Stop heating and allow the temperature of the slurry obtained in the previous step to drop below 50°C. Slowly add the pretreated chitosan acid solution to the reactor and stir thoroughly for 15 minutes to ensure uniform mixing. Slowly add the pH adjuster—triethanolamine (TEA)—to initially adjust the pH of the system to 8.5-9.

0. Slowly add the nanocellulose (CNF) gel and switch to a high-shear disperser. Shear disperse at a speed of at least 2000 rpm for 20-30 minutes to ensure complete dispersion of CNF without agglomeration and a significant increase in system viscosity. S4. pH Adjustment: Continue to slowly add TEA, stirring and cooling continuously below 50°C, and precisely adjust the pH of the entire system to the core reaction range of 9.5 to 10.5, confirming with precision pH test paper or pH meter; S5. Introduce a core cross-linking network: While stirring at a constant medium speed, slowly add dropwise a 20%-30% (w / v) aqueous solution of 1,3-phenylene glycol diboronic acid dissolved in anhydrous ethanol, and continue the reaction for 15 minutes to allow the dynamic covalent crosslinking reaction to proceed in its initial stage. S6. Add auxiliary cross-linking agents and preservatives: Add the pre-prepared borate premix, then add copper sulfate and catechol, maintain the system temperature <50℃, and continue stirring for 20 minutes; S7. Construction of Ion Networks and Functionalization: Slowly add the pre-dispersed magnesium hydroxide suspension and stir thoroughly for at least 3 minutes to ensure that the magnesium ions are evenly dispersed and fully interact with the network. S8. Final Adjustment and Discharge: Add the remaining deionized water, adjust the final solid content of the system to 20%–25 wt%, test the pH again to ensure it is still within the range of 9.5–10.5, stop stirring, cool to room temperature, discharge, filter, obtain the final product, and seal and package it.

10. The method of using a multi-layer composite network adhesive for corrugated cardboard according to claim 1, characterized in that... The application method includes the following steps: First, apply the adhesive evenly by roller coating onto the corrugated peaks; Second, allow it to age in the air for about 1-3 minutes. The third step is to bond the inner and outer paper together; the fourth step is to heat-press and cure the paper, with a temperature of 120℃~150℃ and a pressure of 0.5~1.5MPa for 90-180 seconds; the fifth step is to cool and set the paper.

Citation Information

Patent Citations

  • Sizing-adhesive composition

    CN102471653A

  • High-performance glue

    CN105950071A

  • A corrugated board comprising an adhesive comprising starch and fine micofibrillated cellulose

    CN110088220A

  • PH-responsive chitosan medical biological adhesive as well as preparation and application methods thereof

    CN119405872A

  • Natural adhesive taking coconut pectin biomass as raw material and preparation method thereof

    CN120484722A